Peningkatan Kecepatan (Speed) melalui Penggunaan Aplikasi Smartphone pada Futsal - Faozi, Faiz; Hidayatulloh, Dede Taufik; Rahmawan, Dery (SPRINTER: Jurnal Ilmu Olahraga, 2024)
This study aim to determine how much influence the use of the Nike Training Club (NTC) smartphone application has on increasing speed in futsal extracurricular player at MAN 2 Kota Sukabumi. The type research used in this study is an experiment with a one group pre-test post-test design. The instrument used was a 30meter acceleration test. The subjects of this study were 12 students using the purposive sampling technique. The result of data analysis showed an increase in speed futsal players after receiving treatment using the Nike Training Club (NTC) application, from a value of t=10,009 and Sig. 0,000<0,05 and had a significant effect with an average pre test of 5,22 and an average post-test of 4,56 or an increase of 11.8%. based on the results, there is an effect of using the Nike Training Club (NTC) application on increasing the speed of futsal players at MAN 2 Kota Sukabumi.